Synthesis of arts in the poetry of Maxim Bogdanovych (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The work of the belarusian literature’s classic Maxim Bahdanovich is regarded with a point of view the interaction of the different art’s kinds. The main attention is paid to the correlation of the verbal and visual components in the poet’s works, to the role which plays the rhythm-intonational organization of the verse. M. Bahdanovich’s poetry is the prominent example of the artistic integrity. Lyric meditations and plastic images are harmonically combined in it. The using by belarusian poet other arts’ possibilities is connected with his world outlook’s peculiarities and aesthetic views.
Keywords: Lyric meditations; aesthetic views; peculiarities